2009
DOI: 10.1007/s11146-009-9167-1
|View full text |Cite
|
Sign up to set email alerts
|

Home Price, Time-on-Market, and Seller Heterogeneity Under Changing Market Conditions

Abstract: Home price, Time-on-market, Seller heterogeneity, Market conditions,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
(51 reference statements)
1
17
0
1
Order By: Relevance
“…4 Of course, the investors can always choose to sell the real estate immediately or quickly. However, the would-be return from the immediate sale is expected to be much lower, see Lin and Vandell (2007), Cheng et al (2008), Lin and Liu (2008), and Cheng et al (2009). In addition, Lippman and McCall (1986) have shown that the immediate sale of an illiquid asset is generally not optimal.…”
Section: A Theory Of Optimal Holding Periodmentioning
confidence: 99%
“…4 Of course, the investors can always choose to sell the real estate immediately or quickly. However, the would-be return from the immediate sale is expected to be much lower, see Lin and Vandell (2007), Cheng et al (2008), Lin and Liu (2008), and Cheng et al (2009). In addition, Lippman and McCall (1986) have shown that the immediate sale of an illiquid asset is generally not optimal.…”
Section: A Theory Of Optimal Holding Periodmentioning
confidence: 99%
“…bids are {X1,...,Xn}. The buyers' arrival follows an exogenous and homogeneous Poisson process with the rate λ. Adams, Kluger and Wyatt (), Lin and Vandell (), Lin and Liu () and Cheng, Lin and Liu (), among others, use the same arrival process in their models. There are several well‐known properties of a homogeneous Poisson process (see, e.g ., Kao ).…”
Section: The Modelmentioning
confidence: 99%
“…The seller accepts the first bid. Lin and Liu () and Cheng, Lin and Liu () use similar settings. However, they do not explicitly consider holding cost, so P* is exogenous in their models.…”
Section: The Modelmentioning
confidence: 99%
“…Merlo and Ortalo-Magne (2004) have also looked at posted price changes and found that when reductions in asking price occur, they are generally substantial rather than incremental. Cheng et al (2009) review rents studies of the relationship between asking price and TOM in housing markets, they conclude that there is convincing evidence that a negative relationship exists.…”
Section: Empirical Literaturementioning
confidence: 99%
“…As noted by Arnott (1989) "It will be of interest to examine how the behavior of the market differs when it is either growing or contracting, or when it is subject to anticipated or unanticipated shocks and policy changes." (Arnott, 1989, p. 23) One contribution in this direction is Cheng et al (2009), who studies the effects of changing market conditions on sale prices and TOM in the presence of heterogeneously constrained sellers. …”
Section: Theoretical Literaturementioning
confidence: 99%